2013
DOI: 10.1002/celc.201300016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Electrocatalytic Oxidation of Alcohols by TEMPO and NHPI

Abstract: Kinetic studies and optimization are of interest as essential steps in the field of catalysis. We performed a complementary study of the electrocatalytic performances of (2,2,6,6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO) and N‐hydroxyphthalimide (NHPI) towards alcohol oxidation by using voltammetry as a versatile and informative technique. Both organocatalysts exhibited a good and well‐defined electrocatalytic activity in aqueous solution. Investigations of the efficacy of the reaction conditions revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 49 publications
6
71
1
Order By: Relevance
“…Karimi and co‐workers have shown that, in the presence of alcohols, the oxoammonium ion is regenerated through the direct oxidation of the hydroxylamine reduced form of TEMPO, via a two‐electron‐transfer process at the electrode surface . By comparing the oxidation peak currents in the presence of alcohols to their values in the absence of alcohols (a measure of the catalytic activity of electrogenerated oxoammonium ion) at the same alcohol and TEMPO concentrations at pH 9.6, identified as the optimum and most informative kinetically controlled condition, the team also confirmed the remarkable difference in reactivity of the nitrosonium ion toward the oxidation of primary alcohols, in comparison to secondary alcohols (Figure ).…”
Section: A Versatile Oxidation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimi and co‐workers have shown that, in the presence of alcohols, the oxoammonium ion is regenerated through the direct oxidation of the hydroxylamine reduced form of TEMPO, via a two‐electron‐transfer process at the electrode surface . By comparing the oxidation peak currents in the presence of alcohols to their values in the absence of alcohols (a measure of the catalytic activity of electrogenerated oxoammonium ion) at the same alcohol and TEMPO concentrations at pH 9.6, identified as the optimum and most informative kinetically controlled condition, the team also confirmed the remarkable difference in reactivity of the nitrosonium ion toward the oxidation of primary alcohols, in comparison to secondary alcohols (Figure ).…”
Section: A Versatile Oxidation Methodsmentioning
confidence: 99%
“…Some of us have recently provided arguments for which sol‐gel electrodes functionalized with TEMPO are likely to soon find practical application in the oxidation of alcohols . Studying the mechanism of alcohol electrocatalytic oxidation mediated by TEMPO, Karimi and co‐workers, in 2014, identified the optimum conditions under which to obtain excellent yields in preparative conversions of widely different alcohols . More recently, Stahl and Badalyan reported that the electrochemical alcohol oxidation with an equimolar catalytic amount of (2,2′‐bipyridine)Cu I and TEMPO proceeds at an electrode potential a half‐volt lower than that used for the TEMPO‐only process (with even much faster rates) …”
Section: Introductionmentioning
confidence: 99%
“…The reaction of benzyl alcohol with TEMPO + is the overall intrinsic reaction rate-determining step [36], it can be considered that the reaction rate constant k r of benzyl alcohol with ClO À is about 28 L mol À1 s À1 [37]. In general, a reaction can vary from chemical very fast and thus mass transfer limited (Ha > 3), to extremely slow, only controlled by chemical kinetic reaction (Ha < 0.03) [35].…”
Section: The Reaction Rate-controlling Stepmentioning
confidence: 99%
“…The class of these organocatalyst reagents also includes TEMPO and TEMPO derivatives . A comparison of TEMPO reactivity versus PINO reactivity has been reported for alcohol oxidation and for cellulose oxidation . The tetrachloro‐derivative of phthaloimido‐N‐oxyl (Cl 4 PINO see Reaction Scheme ) has attracted particular attention based on the ability to perform benzylic and allylic C−H hydrogen abstraction with the benefit of fragile carbon structures (e. g. in α‐pinene) being retained and converted directly into valuable products (e. g. to verbenone).…”
Section: Introductionmentioning
confidence: 99%
“…Rafiee et al. reported a detailed study directly comparing the reactivity of TEMPO and PINO for alcohol oxidations . In 1998 Gorgy and coworkers demonstrated oxidation of primary and secondary alcohols with phthalimido‐ N ‐oxyl mediators including the tetrachloro derivative Cl 4 PINO .…”
Section: Introductionmentioning
confidence: 99%